Quercetin alleviates LPS/iE-DAP-induced liver injury by suppressing ferroptosis via regulating ferritinophagy and intracellular iron efflux - Hongzhu Zhang; Huimin Shi; Xuerui Li; Shendong Zhou; Xiaokun Song; Nana Ma; Meijuan Meng; Guangjun Chang; Xiangzhen Shen (Redox Biology)
Ruminal dysbiosis-induced liver injury is prevalent in dairy cows, yet its underlying mechanisms remain incompletely understood. Ferroptosis, a newly identified form of programmed cell death distinct from apoptosis and necrosis, has been implicated in various liver diseases by emerging studies. In the present study, lipopolysaccharide (LPS) and γ-D-glutamyl‐meso‐diaminopimelic acid (iE-DAP) were employed to establish in vitro and in vivo models of liver injury using bovine hepatocytes and mice, respectively. It was observed that noncytotoxic iE-DAP alone did not influence lipid peroxidation or GPX4, but exacerbated LPS-induced ferroptosis and hepatocyte injury. Notably, co-treatment with LPS and iE-DAP (LPS/iE-DAP)-induced hepatocyte injury was mitigated by intervention with the ferroptosis inhibitor ferrostatin-1 (Fer-1). Mechanistically, the activated IL-6/STAT3 signaling pathway was found to mediate LPS/iE-DAP-induced ferroptosis. Suppression of IL-6/STAT3, either through IL6 and STAT3 knockdown or pharmacological intervention, reduced Fe2+ accumulation and alleviated ferroptotic cell death. Further investigations identified that IL-6/STAT3 signaling enhanced ferritinophagy and impaired iron export. Either disrupting ferritinophagy by knocking down NCOA4 or restoring iron export via HAMP knockdown relieved intracellular iron overload and inhibited ferroptosis. Specifically, LPS/iE-DAP treatment increased the interaction between hepcidin and ferroportin, promoting ferroportin ubiquitination and degradation, thereby blocking iron efflux. Furthermore, we provided several evidence to prove that quercetin pretreatment alleviated LPS/iE-DAP-induced ferroptosis and liver injury by decreasing hepatic iron accumulation via targeting the IL-6/STAT3 signaling in vitro and in vivo, effects reversed by the addition of recombinant bovine IL-6. Based on these findings, we concluded that LPS/iE-DAP-induced liver injury by triggering ferroptosis through regulating IL-6/STAT3/ferritinophagy-dependent iron release and IL-6/STAT3/hepcidin/ferroportin-dependent iron export, while quercetin could alleviate this liver injury by inhibiting ferroptosis via IL-6/STAT3 signaling pathway. This study provides novel insights into the mechanisms whereby ruminal dysbiosis induces liver injury and presents a prospective solution for ruminal dysbiosis-induced liver injury.